Starch distribution in sago palm (Metroxylon spp) trunk in East Luwu Regency - Rian Prasetyo; Muhammad Hasjim Bintoro; Sudradjat (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Sago is a starch-producing palm plant often found in marshland or peatland utilized by the community as food. East Luwu Regency is one of the areas where sago plants can be found. The purpose of this study was to determine sago starch distribution on the trunk of sago plants. The research methods used were interviews with farmers as key informants (qualitative) and direct observation of sago plants (quantitative). This study used 18 sago plant samples from two types of sago accessions, namely Uwwu accessions and Battang accessions, obtained from 3 sub-districts: Wotu, Kalaena, and Mangkutana. Sago morphological characteristics observed include plant height, trunk diameter, trunk circumference, pith weight, and dry starch weight. The circumference and diameter of the sago trunk varied among the lower, middle, and upper parts. The results showed that in Battang in Kalaena 3, the middle had a smaller diameter and trunk circumference compared to the lower and upper trunk but had the largest dry starch weight of 29.45 g, compared to the lower trunk (25.21 g) and the upper trunk (22.43 g). The environment is a factor that significantly influences the size of trunk circumference, trunk diameter, and starch content in sago plant trunk. Keywords: accession; Battang; pith; qualitative; starch; Uwwu